2021
DOI: 10.3390/cancers13102403
|View full text |Cite
|
Sign up to set email alerts
|

Aldo-Keto Reductase 1C3 Mediates Chemotherapy Resistance in Esophageal Adenocarcinoma via ROS Detoxification

Abstract: Esophageal adenocarcinoma (EAC) is one of the most lethal malignancies, and limits promising treatments. AKR1C3 represents a therapeutic target to combat the resistance in many cancers. However, the molecular mechanism of AKR1C3 in the chemotherapy resistance of EAC is still unclear. We found that the mRNA level of AKR1C3 was higher in EAC tumor tissues, and that high AKR1C3 expression might be associated with poor overall survival of EAC patients. AKR1C3 overexpression decreased cell death induced by chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that AKR1C3 promoted tumor proliferation and may be correlated with the phosphorylation of AKT ( 20 , 21 ). We found that the mRNA level of AKT was upregulated obviously in sorafenib-resistant patients compared with sorafenib-sensitive patients ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that AKR1C3 promoted tumor proliferation and may be correlated with the phosphorylation of AKT ( 20 , 21 ). We found that the mRNA level of AKT was upregulated obviously in sorafenib-resistant patients compared with sorafenib-sensitive patients ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 98%
“…The activation of the AKT signal was often shown to be related to the treatment outcome, and it has been observed that it leads to resistance to chemotherapy and radiation therapy ( 36 , 37 ). AKT phosphorylation was regulated by AKR1C3 and might be responsible for eliminating over-produced ROS in esophageal adenocarcinoma (EAC) cells ( 20 ). The intracellular ROS levels were induced by cadmium treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of cisplatin is a complex process in which several pathways are involved, leading to cell cycle arrest, apoptosis, ferroptosis, and autophagy, depending on the treatment conditions and the cell type [26][27][28]. Cisplatin-induced cell death via apoptosis is the predominant pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that cisplatin could induce ROS generation in KATO cells in a way that was dependent upon the activity of AKR1C1 and 1C3. Nrf2 is a transcriptional factor that is activated by modification of Cys thiols in Keap1 in response to activators such as ROS, electrophiles, and nitrogen radicals [28,36]. Moreover, a previously published report stated that AKR1C3 is said to be a direct target of Nrf2 and plays an essential role in redox balance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AKR1C1 is associated with cisplatin-resistance in colon cancer cell, head and neck squamous cell carcinoma, nasopharyngeal carcinoma, and paediatric T-cell acute lymphoblastic leukemia [ 30 , 31 , 32 , 33 ]. It has been recently reported that AKR1C3 mediates chemotherapy resistance in breast cancer and esophageal adenocarcinoma [ 34 , 35 ]. Thus, AKR1C isoforms may be a potential target for preventing the development of anticancer drug resistance.…”
Section: Introductionmentioning
confidence: 99%